Spectrophotometric Determination of Tranexamic Acid by Azo-Dye Formation-Application to Pharmaceutical Preparations - Mohamed Dhamra (College of Education for Pure Sciences, 1999)
Abstract A simple and sensitive spectrophotometric method was developed for the determination of tranexamic acid in bulk and pharmaceutical preparations.The method is based on the coupling of each of diazotised p-nitroaniline and diazotised sulphanilic acid with tranexamic acid to form a reddish-orange azo-dye which absorbs maximally at 520 nm with diazotised p-nitroaniline. Beer's law was obeyed within (0.1-7.5) ppm with a molar absorptivity 4.2×104 l.mole-1.cm-1 and yellow azo-dye which absorbs maximally at 420 nm with diazotised sulphanilic acid.Beer's law was obeyed within (0.5-10) ppm with a molar absorptivity 3.3×103 l.mole-1.cm-1. All variables were studied to optimise the reaction conditions. No interference was observed in the presence of common pharmaceutical excipients. The validity of method was tested by analyzing tranexamic acid in its pharmaceutical preparations and good recoveries were obtained.